Exploration of Local Wisdom Values Jaran Kepang Dance: A Case Study at Elementary School - Cahyati, Aghneta Putri; Nurharini , Atip (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This study aims to explore the integration of local wisdom values into the extracurricular learning of the Jaran Kepang dance at Randuacir 3 Elementary School, motivated by the impact of globalisation and students’ declining appreciation for traditional arts. Employing a qualitative descriptive approach with a case study method, the research involved dance trainers, students, and extracurricular dance coordinator teachers as participants. Data were collected through observations and interviews, focusing on aspects such as the philosophy of the dance, the meaning of movements, floor patterns, choreographic design, and the incorporation of local wisdom within each element of the dance. The findings reveal that the Jaran Kepang dance serves as an effective medium for instilling local wisdom values in students. This study contributes to the preservation and development of traditional dance education by offering a comprehensive documentation of local wisdom values embedded in Jaran Kepang, which can serve as a valuable reference for elementary-level cultural learning.